Seasonal Variability in The Implantations of Cardiovascular Electronic Devices - Watanabe, Eiichi; Kiyono, Ken; Harada, Masahide; Ozaki, Yukio (Cardiology and Cardiovascular Medicine, 2019)
Background: Countless studies have found a substantial seasonal variation in cardiovascular disease events, but information about the seasonal variation in implantations of cardiovascular implantable electronic devices (CIEDs) is rare. Objective: We assessed whether there were seasonal variations in CIED implantations. Methods: In this serial cross-sectional study using Japan's National Health Insurance Data, we identified new implants of cardiac pacemakers (PMs, n=402,676) between 2006 and 2016, including implantable cardioverter-defibrillators (ICDs, n=29,330) and cardiac resynchronization therapy with defibrillators (CRT-Ds, n=17,907) between 2009 and 2016. We examined the seasonality in the number of implantations, and whether they depended on the geographical regions (north, central, and south) or number of procedures by prefecture (above and below the mean). A seasonaltrend decomposition procedure based on a locally weighted regression was used to assess the seasonal, monthly or quarterly variations. In addition, the seasonal sinusoidal oscillation in the detrended variations was evaluated using a least-squares cosine-curve fitting algorithm. Results: There were significant seasonal variations in PM implantations with a peak in July and trough in January (p<0.001). CRT-D implantations also had seasonal variations with a peak in June and troughs in January and September (p<0.001). There was no statistically significant seasonal variation only for ICD implantations. The monthly variations in the three types of CIEDs were not influenced by the geographic region or prefectural procedure volume. Conclusion: There were significant seasonal variations in PM and CRT-D implantations with a peak occurring in the summer and trough